Structure and Magnetic Properties of PZT/CoCr Heterostructures - Hong, Nguyen Thi Minh; Thang, Pham Duc; Ha, Pham Thai (Communications in Physics, 2014)
The microstructure, crystallographic structure and magnetic properties of ferroelectric-ferromagnetic PZT/CoCr heterostructures have been investigated by using XRD, SEM and VSM.~Upon applying an electric field, the in-plane magnetization of the heterostructures decreases at various bias magnetic fields. The change in magnetization and the magnetization reversed voltage were obtained. The results demonstrate that the change in magnetic anisotropy can be controlled by electric field via strain-mediated magnetoelectric coupling.